Effect of Inflation on Economic Growth in Sierra Leone Alpha Bernard Bangura (Global Journal of Management and Business Research, 2020)
Introduction-Economic growth is a key policy objective of any government. In addressing the pertinent issues in economic management, experts and economic planners have had to choose between or combine some of the macroeconomic variables. Economic growth, which is measured by Gross Domestic Product (GDP) confers many benefits which include raising the general standard of living of the population as measured by per capita national income, making income distribution easier to achieve, enhance time frame of accomplishing the basic needs of man to a substantial majority of the population. (Barnes, 2017)